2012
DOI: 10.1073/pnas.1211162109
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of human-induced C erosion and burial on soil–atmosphere C exchange

Abstract: Carbon exchange associated with accelerated erosion following land cover change is an important component of the global C cycle. In current assessments, however, this component is not accounted for. Here, we integrate the effects of accelerated C erosion across point, hillslope, and catchment scale for the 780-km 2 Dijle River catchment over the period 4000 B.C. to A.D. 2000 to demonstrate that accelerated erosion results in a net C sink. We found this longterm C sink to be equivalent to 43% of the eroded C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
2
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 36 publications
4
115
2
3
Order By: Relevance
“…In soils, only glucosamine (GluN), galactosamine (GalN), and muramic acid are found in quantifiable concentrations. AS provide a generally readily available energy source for microorganisms and are easy to decompose compared to more recalcitrant organic matter such as lignin or lipids (Amelung et al, 2001(Amelung et al, , 2008von Luetzow et al, 2006;Roberts et al, 2007;Schmidt et al, 2011). AS turnover is, therefore, fast compared to other stabilized SOC fractions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In soils, only glucosamine (GluN), galactosamine (GalN), and muramic acid are found in quantifiable concentrations. AS provide a generally readily available energy source for microorganisms and are easy to decompose compared to more recalcitrant organic matter such as lignin or lipids (Amelung et al, 2001(Amelung et al, , 2008von Luetzow et al, 2006;Roberts et al, 2007;Schmidt et al, 2011). AS turnover is, therefore, fast compared to other stabilized SOC fractions.…”
Section: Introductionmentioning
confidence: 99%
“…For details on the gathered fractions see the original study and the concepts of Six et al (1998Six et al ( , 2002. In short, the scheme consists of a series of chemical and physical fractionation techniques applied to isolate functional SOC fractions, differentiated by stabilization mechanisms (chemical, biochemical and physical) which can also be associated with different (potential) turnover times (see also von Luetzow et al, 2006). Background information to the key soil and geomorphological properties as well as the abundance and composition of identified SOC fractions as described by Doetterl et al (2012) and Z. for the investigated soils can be found in Table 1.…”
Section: Soc Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although colluvial soils may therefore store more C than non-eroding soils, the rate at which the buried SOC cycles remains poorly quantified: on the one hand, 137 Cs and C inventory measurements showed that a substantial part of the deposited C in the colluvial soils of first-order catchments is effectively protected on the timescale of 50 yr ; on the other hand, studies covering millennial timescales showed that colluvial sediments on the Belgian loess belt that were deposited several centuries to millennia ago are typically depleted in SOC relative to the source areas (e.g. Vancampenhout et al, 2008;Van Oost et al, 2012), indicating that the deposited C in colluvial soils is at least partially mineralised on the timescale of several centuries.…”
Section: Z Wang Et Al: the Fate Of Buried Organic Carbon In Colluvimentioning
confidence: 99%
“…Colluvial soils therefore may be interpreted as chronostratigraphy in which young deposits are found at shallow depth and sediment age increases with depth (Van Oost et al, 2012). The efficiency of C burial can then be regarded as the fraction of deposited C that is preserved in the buried sediments.…”
Section: Burial Efficiencymentioning
confidence: 99%